The recognition of letters in emergent literacy in German: evidence from a longitudinal study. (2nd June 2017) - Schmitterer, Alexandra M.A.; Schroeder, Sascha
Abstract : Background: German children do not formally learn letter‐sounds before school entry. In this study, we evaluated kindergarten children's sensitivity to the frequency of letters and visually similar symbols in child‐directed texts, how it develops and whether it predicts early reading abilities. Method: In a longitudinal study from kindergarten to primary school, children were asked to judge whether a presented alphabetic (e.g., A ) or non‐alphabetic symbol (e.g., # ) was a letter. High and low frequency was varied for both types of symbols. Furthermore, we analysed whether later reading abilities were predicted by this letter judgement ability. Results: Before school entry, children had difficulties in distinguishing frequent non‐alphabetic symbols from letters. Furthermore, letter judgement in kindergarten predicted reading abilities in first grade. Conclusions: Children derive some knowledge about letters from the frequency of co‐occurrence of letters and symbols in texts. The ability to distinguish letters from non‐alphabetic symbols predicts early reading.